Relationship between the kick start performance and the isometric / isokinetic muscular strength in competitive swimming - Suito, H.; Ozeki, K.; Nunome, H.; Ikegami, Y. (Japanese Journal of Sciences in Swimming and Water Exercise, 2015)
The purpose of this study was to clarify the relationship between the kick start performance and legs muscular strength in competitive swimming. Six male competitive swimmers performed maximal efforts in 20 m of front crawl swimming using kick start. The start time was measured as the time when swimmer`s head passed across 5 m line using a digital camera operating at 30 Hz. Moreover, the starting movements were recorded by a high speed camera (100 Hz) and the 2-DLT method was used for calculating the kinematical data. The maximal voluntary isometric and isokinetic (60 deg/s, 120 deg/s) knee extension moments of front and rear legs were determined by using an isokinetic dynamometer. High correlation coefficients (r = -0.821, P < 0.05, r = 0.962, P < 0.01) were observed between the start time, the horizontal velocity of center of mass at take-off and the isometric knee extension moment of front leg, whereas there was no significant correlation for the other parameters. These results of this study suggested a possibility some trainings for isometric strength of the front leg would improve the resultant start performance.